Cybernetic Collaborations, Literature Machines and Italo Calvino's ‘L’incendio della casa abominevole'. - Cronin, Susie (Italianist, 2017)
This article explores two collaborations that influenced Italo Calvino's short story, ‘L’incendio della casa abominevole', the first an anticombinatoric project and collaboration undertaken with Paul Braffort of the French group Oulipo (Ouvroir de littérature potentielle) in 1973, and the second with the former IBM programmer, William Skyvington, in early 1977. In the case of the latter interaction, a hitherto unknown epistolary exchange between Calvino and Skyvington is examined in order to understand the terms in which Calvino's ambitions and the programmer's doubts were expressed, and the reasons for which a subsequent collaboration was not undertaken. The response Calvino received from Skyvington is finally brought to bear on Calvino's later work and correspondence, in which the limitations articulated by Skyvington are interpreted as influencing the nature of the Italian author's later projects.